Evaluation of the Disease Activity index for PSoriatic Arthritis (DAPSA) with a quick quantitative C reactive protein assay (Q-DAPSA) in patients with psoriatic arthritis: a prospective multicentre cross-sectional study - Denis Poddubnyy; Hildrun Haibel; Fabian Proft; Mikhail Protopopov; Valeria Rios Rodriguez; Murat Torgutalp; Judith Rademacher; Silke Zinke; Henning Christian Brandt; Kirsten Karberg; Burkhard Muche; Gerd Rüdiger Burmester; et al. (RMD Open, 2022)
Objectives This study aimed to evaluate the Disease Activity index for PSoriatic Arthritis (DAPSA) based on a quick quantitative C reactive protein (qCRP) assay (Q-DAPSA) in a multicentre, prospective, cross-sectional study in patients with psoriatic arthritis (PsA).Methods The assessment of prospectively recruited study patients included joint examination and patient reported outcome (PRO) measures (patient global assessment, patient pain assessment). Following, the DAPSA based on a routine laboratory CRP measurement, Q-DAPSA and clinical DAPSA (cDAPSA) were calculated. Cross-tabulations and weighted Cohen’s kappa were performed to analyse the agreement of disease activity categories. Bland-Altman plots and intraclass correlation coefficients were used to determine the agreement of numerical values regarding CRP and qCRP as well as different disease activity scores.Results Altogether, 104 patients with PsA could be included in the statistical analysis. With Q-DAPSA, 102 of 104 (98.1%) patients achieved identical disease activity categories in comparison to DAPSA with a weighted Cohen’s kappa of 0.980 (95% CI: 0.952 to 1.000). The agreement between DAPSA and cDAPSA was slightly lower with identical disease activity categories seen in 97 of 104 (93.3%) of patients and with a weighted Cohen’s kappa of 0.932 (95% CI 0.885 to 0.980).Conclusions The Q-DAPSA showed an almost perfect agreement with the conventional DAPSA regarding identical disease activity categories. Thus, the Q-DAPSA can be used as a timely available disease activity score in patients with PsA with the additional benefit of CRP involvement. Consequently, the Q-DAPSA could facilitate the implementation of the treat-to-target concept in clinical routine and clinical trials.